Tet2-mediated clonal hematopoiesis modestly improves neurological deficits and is associated with inflammation resolution in the subacute phase of experimental stroke - Evans, Megan A.; Chavkin, Nicholas W.; Sano, Soichi; Sun, Hanna; Sardana, Taneesha; Ravi, Ramya; Doviak, Heather; Wang, Ying; Yura, Yoshimitsu; Polizio, Ariel H.; Horitani, Keita; Ogawa, Hayato; et al. (Frontiers in Cellular Neuroscience, 2024)
Introduction Recent work has revealed that clonal hematopoiesis (CH) is associated with a higher risk of numerous age-related diseases, including ischemic stroke, however little is known about whether it influences stroke outcome independent of its widespread effects on cardiovascular disease. Studies suggest that leukocytes carrying CH driver mutations have an enhanced inflammatory profile, which could conceivably exacerbate brain injury after a stroke. Methods Using a competitive bone marrow transplant model of Tet2-mediated CH, we tested the hypothesis that CH would lead to a poorer outcome after ischemic stroke by augmenting brain inflammation. Stroke was induced in mice by middle cerebral artery occlusion and neurological outcome was assessed at acute (24 h) and subacute (14 d) timepoints. Brains were collected at both time points for histological, immunofluorescence and gene expression assays. Results Unexpectedly, Tet2-mediated CH had no effect on acute stroke outcome but led to a reduction in neurological deficits during the subacute phase. This improved neurological outcome was associated with lower levels of brain inflammation as evidenced by lower transcript levels of various inflammatory molecules alongside reduced astrogliosis. Discussion These findings suggest that Tet2-mediated CH may have beneficial effects on outcome after stroke, contrasting with the conventional understanding of CH whereby leukocytes with driver mutations promote disease by exacerbating inflammation.